Hepatitis B virus X protein stimulates high mobility group box 1 secretion and enhances hepatocellular carcinoma metastasis. (28th May 2017) - Chen, Shuzhen; Dong, Zihui; Yang, Pinghua; Wang, Xianming; Jin, Guangzhi; Yu, Han; Chen, Lei; Li, Liang; Tang, Liang; Bai, Shilei; Yan, Hexin; Shen, Feng; et al.
Abstract: Hepatitis B virus X protein (HBx) plays an important role in the progression of hepatocellular carcinoma. Here we reported that overexpression of HBx in hepatocellular carcinoma (HCC) cells could induce the secretion of high-mobility group box 1 (HMGB1) to promote invasion and metastasis of HCC in an autocrine/paracrine manner. HBx triggered an increase of cytoplasmic calcium and activated CAMKK/CAMKIV pathway, leading to subsequent translocation and release of HMGB1. HMGB1 neutralizing antibody, as well as calcium chelator or inhibitors of CAMKK/CAMKIV, could remarkably reduce invasion and metastasis of HCC cells in vitro and in a murine HCC metastasis model in vivo . Furthermore, the level of HMGB1 in patient serum and tumor tissues was positively correlated with HBV DNA load. We demonstrate an inverse relationship between HMGB1 in tumor cytoplasm and overall prognosis of HCC patients. Conclusion: HBx promotes the progression of HCC through translocation and secretion of HMGB1 from tumor cells via calcium dependent cascades. These data indicates that HMGB1 could serve as a novel prognostic biomarker and potential therapeutic target for HBV-related HCC. Highlights: HBx induced the secretion of HMGB1 in HCC tumor cells. HMGB1 secretion facilitates the invasion and metastasis of HCC cells. HBx triggers the secretion of HMGB1 via CAMKK/CAMKIV pathway. HMGB1 secretion inversely correlates with prognosis of HCC patients. HMGB1 could serve as a potential therapeutic target for HBV-related HCC.